RAPD and SDS-PAGE analysis of Mycoplasma hyorhinis isolates of South Korea - BARATE, ABHIJIT KASHINATH; JANG, GYUSEONG; CHO, SEONG BEOM; HAHN, TAE-WOOK (The Indian Journal of Animal Sciences, 2014)
In this study, 25 field isolates recovered from 14 herds were analysed using SDS-PAGE and RAPD. Among the field strains, variability of 34.2% and 30% were observed at the protein and genomic levels, respectively. Also, variability of 44.9% and 37.7% were noticed between the field strains and a reference strain at the protein and genomic levels, respectively. Furthermore, isolates from the same herd demonstrated differences in protein and RAPD patterns. These results reveal high proteomic and genetic diversity among the field isolates of Mhr in South Korea.